Estimasi Cadangan Karbon Tegakan Dipterocarpaceae Hutan Kerangas dan Kontribusinya terhadap Mitigasi Perubahan Iklim di Kalimantan Tengah - Sari Marlina; Achmad Imam Santoso; Muh Azhari (Lembaga Bale Literasi, 2026)
Kerangas (heath) forests in Kalimantan are dominated by Dipterocarpaceae yet remain underrepresented in regional carbon-stock assessments, despite documented vulnerability to fire during dry-season anomalies. This study estimated the aboveground biomass (AGB) and carbon stock of Dipterocarpaceae stands in a kerangas forest at KHDTK Mungku Baru, Palangka Raya, Central Kalimantan, based on tree-inventory data across 24 sample plots (0.96 ha at the tree growth stage). Fourteen Dipterocarpaceae species from six genera were recorded. Because tree height was not measured in the field, AGB was estimated using diameter- and wood-density-based allometric models (Chave et al., 2005; Basuki et al., 2009), with a lognormal moment-based correction for within-species diameter variance evaluated through Gauss-Hermite quadrature. Estimated AGB ranged from 127.6 to 204.8 Mg/ha depending on model choice, corresponding to 60.0-96.2 Mg C/ha and 220.3-353.2 Mg CO2-eq/ha. Cotylelobium burckii and Shorea seminis contributed the largest share of stand-level carbon; however, a data-consistency check flagged the recorded basal area of S. seminis as statistically improbable, so this estimate is reported conservatively pending field verification. A complementary diversity analysis revealed a regeneration bottleneck at the pole (tiang) stage, raising concern for the resilience of this carbon stock following fire disturbance. These findings underscore the role of kerangas Dipterocarpaceae as a climate-mitigation asset that requires targeted fire-risk management.